2018
DOI: 10.1200/jop.2017.025221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Survival Impact of Pretreatment Cancer-Associated Weight Loss: A Tool for Guiding Early Palliative Care

Abstract: Pretreatment cancer-associated weight loss is common, even in early-stage disease, and is independently associated with reduced survival. Minimal weight loss represents a clinically distinct entity with an associated overall survival intermediate to that of no weight loss and overt wasting. Early diagnosis and treatment of cancer-associated wasting offers a novel therapeutic avenue for reducing cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 20 publications
10
46
2
Order By: Relevance
“…It is observed in up to 50% of patients with solid tumors. 1 Cancer patients with cachexia have a >50% reduction in overall survival when compared with stage-matched patients without cachexia. 1 Even when cachexia is identified in early stage cancer patients, survival is not improved because of a potential lack of effective therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed in up to 50% of patients with solid tumors. 1 Cancer patients with cachexia have a >50% reduction in overall survival when compared with stage-matched patients without cachexia. 1 Even when cachexia is identified in early stage cancer patients, survival is not improved because of a potential lack of effective therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed in up to 50% of patients with solid tumors. 1 Cancer patients with CX have greater than a 50% reduction in overall survival when compared to stage matched patients without cachexia. 1 Even when CX is identified in early stage cancer patients, survival is not improved because of a potential lack of effective therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Cancer patients with CX have greater than a 50% reduction in overall survival when compared to stage matched patients without cachexia. 1 Even when CX is identified in early stage cancer patients, survival is not improved because of a potential lack of effective therapeutic interventions. 2 Although CX has been recognized for more than half a century, most preclinical studies and clinical trials targeting the immune system (TNF-α, IL-6), appetite stimulation, and muscle regeneration have failed to durably improve the syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Involuntary weight loss is a common occurrence among patients with cancer and is often a precursor to cancer diagnosis. In a study by Gannavarapu et al, cancer‐associated weight loss was observed in 34.1% of patients at the time of cancer diagnosis . Because of this early and often prolonged weight loss, it is important to obtain a detailed weight history and evaluate whether the weight loss was indeed intentional as a result of diet or lifestyle interventions, as may be initially reported by the patient, or in fact unintentional and due to other factors.…”
Section: Oncology Patient Populationmentioning
confidence: 99%